2001
DOI: 10.1117/1.1412850
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acetic acid-induced whitening of high-grade squamous intraepithelial lesions

Abstract: Immature and dysplastic cervical squamous epithelium whitens after the application of acetic acid during a colposcopic examination. The whitening process occurs visually over several minutes and subjectively discriminates between dysplastic and normal tissue. In this work, examples of the acetowhitening process are detailed in three ways: the color-imaged colposcopic appearance of the acetowhitening of high-grade cervical intraepithelial neoplasia (CIN 2/3), the kinetics of these reflectance patterns transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Second, referring facilities only provided cytology to la Liga Contra el Cáncer for 28% of patients; thus, cytology was unknown for a majority of cases in our study. Third, acetic acid was not re-applied immediately prior to imaging with the Pocket colposcope until the last 32 patients (22, 26). Revising the study protocol in future studies to re-apply acetic acid between imaging with the two colposcopes could improve visualization of aceto-whitening.…”
Section: Discussionmentioning
confidence: 99%
“…Second, referring facilities only provided cytology to la Liga Contra el Cáncer for 28% of patients; thus, cytology was unknown for a majority of cases in our study. Third, acetic acid was not re-applied immediately prior to imaging with the Pocket colposcope until the last 32 patients (22, 26). Revising the study protocol in future studies to re-apply acetic acid between imaging with the two colposcopes could improve visualization of aceto-whitening.…”
Section: Discussionmentioning
confidence: 99%
“…Reflectance imaging with green wavelength illumination consistently gives best contrast because of hemoglobin absorption39. Alternatively, color reflectance images obtained with white light illumination can be separated into red, green, and blue channels and analyzed to enhance image contrast15, 40. A pilot study of digital reflectance images of the cervix acquired from 29 women showed that an automated image analysis algorithm could identify the presence and spatial extent of high grade precancers with 79% sensitivity and 88% specificity compared to histopathologic analysis 15.…”
Section: In Vivo Optical Imaging Technologiesmentioning
confidence: 99%
“…Imaging the time course of acetowhitening can also improve the ability to discriminate high grade precancer39, 40; a multispectral reflectance imaging study of 123 women found that the increase in light scattering after application of acetic acid was greater and persisted for a longer time in high grade precancers41.…”
Section: In Vivo Optical Imaging Technologiesmentioning
confidence: 99%
“…5,6,8,14 Figure 2 also shows that variations in the actual epithelium thickness do not have a strong effect on the reflectance observed. For this reason, the acetowhite effect is typically observed in the 540 to 580 nm region (green region) where hemoglobin provides strong absorption in the stroma; conversely, it is barely observed at wavelengths longer than 600 nm (red region) where hemoglobin absorption is low.…”
Section: Resultsmentioning
confidence: 83%